2007
DOI: 10.1634/stemcells.2007-0416
|View full text |Cite
|
Sign up to set email alerts
|

Human Mesenchymal Stem Cells Inhibit Neutrophil Apoptosis: A Model for Neutrophil Preservation in the Bone Marrow Niche

Abstract: Antibody neutralization experiments demonstrated that the key MSCderived soluble factor responsible for neutrophil protection from apoptosis was IL-6, which signaled by activating STAT-3 transcription factor. Furthermore, IL-6 expression was detected in MSC by real-time reverse transcriptionpolymerase chain reaction and enzyme-linked immunosorbent assay. Finally, recombinant IL-6 was found to protect neutrophils from apoptosis in a dose-dependent manner. MSC had no effect on neutrophil phagocytosis, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
326
1
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 451 publications
(345 citation statements)
references
References 68 publications
10
326
1
8
Order By: Relevance
“…Interestingly, the expression of IL6 was maintained in MSCs from some donors cultured under hypoxia at levels similar to those in MSCs cultured under normoxia, but it was downregulated in MSCs from other donors. IL6 is involved in the inhibition of monocyte differentiation toward DCs, decreasing their stimulatory effect on T cells (Djouad et al 2007;Jiang et al 2005), while the secretion of IL6 by MSCs delays apoptosis of lymphocytes and neutrophils (Raffaghello et al 2008;Xu et al 2007). Through further investigation, it will be important to determine whether the relative differences in the levels of gene expression between different donors under hypoxia are a critical factor for the selection of potent MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of IL6 was maintained in MSCs from some donors cultured under hypoxia at levels similar to those in MSCs cultured under normoxia, but it was downregulated in MSCs from other donors. IL6 is involved in the inhibition of monocyte differentiation toward DCs, decreasing their stimulatory effect on T cells (Djouad et al 2007;Jiang et al 2005), while the secretion of IL6 by MSCs delays apoptosis of lymphocytes and neutrophils (Raffaghello et al 2008;Xu et al 2007). Through further investigation, it will be important to determine whether the relative differences in the levels of gene expression between different donors under hypoxia are a critical factor for the selection of potent MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, both MSCs and MSC supernatant have been reported to have notable anti-apoptotic eff ects on resting and activated neutrophils. 52 This eff ect does not require direct contact between cells and seems to be mediated partly by MSC production of the anti-apoptotic cytokine interleukin 6 (fi gure). 52 MSC production of FGF7 has also been postulated to inhibit apoptosis of monocytes, leading to increased bacterial killing.…”
Section: Anti-apoptotic Eff Ectsmentioning
confidence: 99%
“…52 This eff ect does not require direct contact between cells and seems to be mediated partly by MSC production of the anti-apoptotic cytokine interleukin 6 (fi gure). 52 MSC production of FGF7 has also been postulated to inhibit apoptosis of monocytes, leading to increased bacterial killing. 41 Future research will hopefully illuminate the extent and signifi cance of this pathway.…”
Section: Anti-apoptotic Eff Ectsmentioning
confidence: 99%
“…Similar to the present study, some former studies also used the bone marrow derived MSCs to investigate the interaction between MSCs and neutrophils. 11,27 Neutrophil homeostasis and turnover are highly regulated in the body. Circulating neutrophils have a short life span of 6-10 h, after which the cells undergo apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that MSCs diminish the mitochondrial pro-apoptotic protein, Bax in neutrophils through IL-6 secretion. 27 It is also known that adenosine produced by MSCs can stimulate the A2B receptors through autocrine or paracrine routs, and potently stimulates IL-6 secretion. 23 According to the antagonistic effects of caffeine on adenosine receptor, it is possible that Fig.…”
Section: Discussionmentioning
confidence: 99%